Upstream color [videorecording (DVD)] - Carruth, Shane; Seimetz, Amy; Sensenig, Andrew; Martins, Thiago (ERBP : New Video, 2013)
Kris is derailed from her life when she is drugged by a small-time thief. She is unknowingly drawn into the life cycle of a presence that permeates the microscopic world, moving to nematodes, plant life, livestock, and back again. Along the way, she finds another being-a familiar, who is equally consumed by the mysterious presence. The two search urgently for a place of safety within each other as they struggle to assemble the loose fragments of their wrecked lives.